A sustainable biopolymer binder enables the fabrication of high-performance ?-MnO2 cathodes for aqueous zinc-ion storage - Sariyer, Selin; Demir-Cakan, Rezan (Royal Soc Chemistry, 2025)
Rechargeable aqueous zinc-ion batteries (ARZIBs) have gained considerable attention as sustainable energy storage systems due to their inherent safety, environmental friendliness, and low cost. Among various cathode candidates, beta-MnO2 is particularly attractive owing to its structural stability and abundance. However, its practical application is hindered by the dissolution of Mn2+ ions during cycling, which leads to poor long-term performance. In this study, beta-MnO2 was synthesized via a hydrothermal method and integrated into electrodes using both conventional PVDF and a novel water-based, cross-linked binder system composed of xanthan gum and citric acid (c-XG-CA). The c-XG-CA binder, abundant in hydroxyl, carboxyl, and acetyl groups, was shown to enhance Mn2+ adsorption capacity, improve electrode adhesion, and increase hydrophilicity compared to PVDF. The formation and stability of the cross-linked structure, along with its manganese ion adsorption behavior, were verified through FTIR and DFT analyses. Electrochemical evaluations revealed that the beta-MnO2-c-XG-CA cathode achieved superior cycling stability (73% capacity retention after 200 cycles at C/2) and higher diffusion coefficients. Post-cycling XRD and SEM characterization studies indicated the formation of reversible Zn-buserite and Znx(OTf)y(OH)2x-ynH2O phases. These findings demonstrate that the c-XG-CA binder offers significant structural and electrochemical advantages, making it a promising alternative to conventional binders for high-performance ARZIBs.
Keywords: Manganese-Dioxide; Xanthan; Electrolyte; Chemistry; Binding